Superdiversiteetti Näkökulmia maahanmuuton monimuotoisuuteen - Martikainen, Tuomas; Pöyhönen, Sari (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2023)
This book is the first Finnish-language collection of research on superdiversity. At the core of the book is the growing migration to Finland since the turn of the 1990s and its numerous effects on Finnish society. The interdisciplinary examination of superdiversity is important at the current moment: Finland as a society has reached the point where certain social categories, such as ethnic background, country of birth, mother tongue or gender, are not necessarily sufficient to understand the increased diversity and its consequences. The book consists of a comprehensive introduction to the topic and thirteen chapters. In Finland, research on superdiversity is carried out especially in critical sociolinguistics and applied language studies, education, cultural studies, social sciences, and urban studies. Therefore, these disciplines are strongly represented in the collection, and the chapters approach a variety of topics including refugees' mental health, experiences of multilingual families, the diversity of education and working life, discursive practices in social media, issues of urban planning and pro-asylum activism.